Towards a Model-Based Methodology for Rating and Monitoring Wear Risk in Oscillating Grease-Lubricated Rolling Bearings - Arne Bartschat; Matthias Stammler; Jan Wenske (Lubricants)
Oscillating grease-lubricated slewing bearings are used in several applications. One of the most demanding and challenging is the rotor blade bearings of wind turbines. They allow the rotor blades to be turned to control the rotational speed and loads of the complete turbine. The operating conditions of blade bearings can lead to lubricant starvation of the contacts between rolling elements and raceways, which can result in wear damages like false brinelling. Variable oscillating amplitudes, load distributions, and the grease properties influence the likelihood of wear occurrence. Currently, there are no methods for rating this risk based on existing standards. This work develops an empirical methodology for assessing and quantifying the risk of wear damage. Experimental results of small-scale blade bearings show that the proposed methodology performs well in predicting wear damage and its progression on the raceways. Ultimately, the methods proposed here can be used to incorporate on-demand lubrication runs of pitch bearings, which would make turbine operation more reliable and cost-efficient.